Kontribusi Naungan Pohon terhadap Kepadatan Cacing Tanah - DWIASTUTI, SRI; SAJIDAN, SAJIDAN (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
This research aims at exploring the contribution of the shade of treetowards the density of earthworms. The convertionof forest into a farmland causeda change in the shade of tree from a closed into an open ecosystem that was predicted to be followed by the decrease of earthworms density. The kinds of land thatis used for research are forest, complex agroforestry, simple agroforestry, teak monoculture, teak-accacia polyculture, and peanut crops. The data were analyzed quantitatively using statistical methods by SPSS 0.16. The results show that the wide oftree shade contributes to the density of earthworms on rainy season as much as 71.5% and also contributes to the density of earthworms on dry season as much as 52.2%. From the results, it can be concluded that the shade of tree has a strong role towards the density of earthworms.